Pengaruh Pengungkit Keuangan dan Profitabilitas Terhadap Perataan Laba Pada Indeks IDX Quality 30 Non Bank Periode 2015-2019 - Fitri Apriani Maudinah; Ali Mutasowifin (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
As management has the authority over the financial statements issued by the company, much of earnings management is trying to overhaul profits or what is called earnings engineering. One of the profit engineering techniques is income smoothing, which rules profits in order to reduce fluctuation. This study aims to analyze the effects of financial leverage and profitability on income smoothing. The object of this research is the IDX Quality 30 index (IDXQ30) Non-Bank for the 2015-2019 period. The data used is secondary data obtained from the companies’ financial statements during the 2015-2019 period and literature studies. The method used in this research is binary logistic regression analysis with Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Net Profit Margin (NPM) as independent variables and Eckel Index as dependent variable. The results showed that simultaneously DER, ROA, and NPM have a significant effect on income smoothing. Partially, DER and ROA have no effect on income smoothing, while NPM variable has a significant negative effect on income smoothing.